Obstacles to Achieving the Goals in the Curriculum of the Social Subject for the Seventh Grade Basic in the Point of View of Educators and Teachers - Mariwan Mohamed Abdulrahman; Miqdad Hussein Taha (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study aimed to identify the obstacles to achieving the goals in the curriculum of the social subject for the seventh grade basic in the point of view of educators and teachers in the city of Erbil for the academic year (2021-2022), from the point of view of: Identify differences in statistical significance and differences in statistical significance in the social curriculum for the seventh grade from the point of view of educational supervisors and teachers in Erbil city, for variables (sex and experiences interaction between supervisors and teachers).The research community is made up of supervisors and teachers of the seventh grade social studies of both sexes (male) and female, the researcher was taken to the community randomly, consisting of (8) supervisors and (100) teachers of the subject of sociology for the seventh grade basic, to achieve the objectives of the study used the researcher descriptive curriculum. In order to prepare the study tool, the researcher benefited from sources consisting of the parameters of the constraints of the social book i took. Which we adapted to the environment of society, and the researcher reaffirms the sincerity of the tool, by distributing the questionnaire form to (11) experts and specialists from Salaheddine University, as well as from the stability and sincerity of the tool, the researcher distributed the research tool to 45 teachers from the community of origin, and then implemented the stability of the research tool by the program (SPSS) Which consisted of 40 lines and in the last 31 lines and became the study tool of five areas.